Lenticulostriate Artery Aneurysm Associated with Cerebral Arteriovenous Malformation: Report of Rare Association and Its Endovascular Management - Kannath, Santhosh Kumar; Rajan, Jayadevan Enakshy (Journal of Clinical Interventional Radiology ISVIR, 2017)
Aneurysms involving the lenticulostriate arteries are rare and are described in the literature in small case series or single-case reports. In this report, we discuss a case of a young woman who presented with acute lateral ventricular bleed and was found to have an arteriovenous malformation within the corona radiata and an aneurysm involving the distal lenticulostriate artery. The aneurysm was treated successfully by endovascular embolization. In deep-seated arteriovenous malformations (AVMs) that are conventionally treated by stereotactic radiosurgery, a targeted approach for treatment of an associated aneurysm could be considered to reduce the risk of rebleed until the AVM is obliterated.
Keywords: lenticulostriate artery aneurysm; cerebral arteriovenous malformation; endovascular embolization